Benign tumors in myotonic dystrophy type I target disease‐related cancer sites. Issue 8 (26th July 2019) - Alsaggaf, Rotana; St. George, Diane Marie M.; Zhan, Min; Pfeiffer, Ruth M.; Wang, Youjin; Anderson, Lesley A.; Liu, Zhiwei; Koshiol, Jill; Bauer, Andrew J.; Wagner, Kathryn R.; Greene, Mark H.; Amr, Sania; et al.
Abstract: Objectives: Recent evidence showed that myotonic dystrophy type I (DM1) patients are at increased risk of certain cancers, but the risk of benign tumors is unknown. We compared the risk of benign tumors in DM1 patients with matched DM1‐free individuals and assessed the association between benign tumors and subsequent cancers. Methods: We identified 927 DM1 patients and 13, 085 DM1‐free individuals matched on gender, birth‐year, clinic, and clinic‐registration year from the UK Clinical Practice Research Datalink, a primary care records database. We used Cox regression models for statistical analyses. Results: DM1 patients had elevated risks of thyroid nodules (Hazard Ratio [HR] = 10.4; 95% Confidence Interval [CI] = 3.91–27.52; P < 0.001), benign tumors of the brain or nervous system (HR = 8.4; 95% CI = 2.48–28.47; P < 0.001), colorectal polyps (HR = 4.3; 95% CI = 1.76–10.41; P = 0.001), and possibly uterine fibroids (HR = 2.7; 95% CI = 1.22–5.88; P = 0.01). Pilomatricomas and salivary gland adenomas occurred almost exclusively in DM1 patients (Fisher's exact P < 0.001). The HR for colorectal polyps was elevated in DM1 males but not in females (HR = 8.2 vs. 1.3, respectively; P ‐heterogeneity < 0.001), whereas endocrine and brain tumors occurred exclusively in females. The data suggested an association between benign tumors and subsequent cancer in classic DM1 patients (HR = 2.7; 95% CI = 0.93–7.59; P = 0.07). Interpretation: Our study showed a similar site‐specific benign tumor profile to that previously reported for DM1‐associated cancers. The possible association between benign tumors and subsequent cancer in classic DM1 patients warrants further investigation as it may guide identifying patients at elevated risk of cancer. Our findings underscore the importance of following population‐based screening recommendations in DM1 patients, for example, for colorectal cancer.